Enhancement of uniform plastic deformation for pure titanium foils by applying pre-strain combining with resistance heating method for microforming - Qiu Zheng; Tsuyoshi Furushima (Journal of Materials Research and Technology, 2020)
Pure titanium (Ti) is usually deformed at elevated temperatures due to its poor formability at room temperature (RT), resulting in its strength reduction after deformation. Applying pre-strain combining with resistance heating (RH) method, which can be conducted at one procedure, was proposed to enhance its plasticity in this work. The influence of the proposed process on tensile deformation of pure Ti foils with 50 μm thick was investigated using a RH assisted tensile testing system. Full strain field was measured by a digital image correlation (DIC) system with laser speckles. Uniaxial tensile pre-strain ranging from 1% to 2% was applied at a low temperature of 160 °C with relatively high nominal strain rates of 10−2 and 10−1 s−1. Then tensile tests were conducted at RT with a nominal strain rate of 10−3 s−1. As results, although the ultimate tensile strength (UTS) slightly decreased with increasing pre-strain, the maximum decreasing rate was within 4%, indicating that the effect of pre-strain on UTS is negligible. The strain distribution analyzed from DIC was relatively uniform at UTS. Uniform elongation increased with increasing pre-strain. The maximum increasing rate achieved 36%. It is confirmed that the heating rate using RH for heating Ti foils with 50 μm thick is about 340 times larger than that for heating Ti sheets with 1 mm thick. The quick response of RH makes it possible for the application of the proposed process to mass production for manufacturing microparts.